2010
DOI: 10.1124/mol.110.066407
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Large-Conductance Ca2+-Activated K+ Channels by Nanomolar Concentrations of Ag+

Abstract: Silver has been widely used in various medical products because of its antibacterial properties. However, there is only limited information concerning silver-related cytotoxicity. In this study we show that Ag ϩ at low nanomolar concentrations (Ͻ10 nM) strongly inhibits the activity of large-conductance Ca 2ϩ -activated K ϩ channels (BK) (Slo1), a widely expressed and physiologically important potassium channel. The Ag ϩ inhibition is caused by irreversible modification on cytosolically accessible parts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For nAChR, the linear free energy analysis has yielded a tremendous amount of insight into the structural details of the arrangement of the pore and how nAChR channels gate ( Grosman et al, 2000 ; Cymes et al, 2002 ), as did the proton-probing method ( Cymes et al, 2005 ; Cymes and Grosman, 2008 , 2011 ). For BK channels, because of a large number of endogenous cysteines, the cysteine scanning approach is problematic ( Tang et al, 2001 ; Zhang and Horrigan, 2005 ; Zhou et al, 2010 ). As we found out in this study, BK channels, possibly because of their large pore size ( Li and Aldrich, 2004 , 2006 ; Brelidze and Magleby, 2005 ; Wilkens and Aldrich, 2006 ; Tang et al, 2009 ), are quite tolerant for large side-chain substitutions in the pore.…”
Section: Discussionmentioning
confidence: 99%
“…For nAChR, the linear free energy analysis has yielded a tremendous amount of insight into the structural details of the arrangement of the pore and how nAChR channels gate ( Grosman et al, 2000 ; Cymes et al, 2002 ), as did the proton-probing method ( Cymes et al, 2005 ; Cymes and Grosman, 2008 , 2011 ). For BK channels, because of a large number of endogenous cysteines, the cysteine scanning approach is problematic ( Tang et al, 2001 ; Zhang and Horrigan, 2005 ; Zhou et al, 2010 ). As we found out in this study, BK channels, possibly because of their large pore size ( Li and Aldrich, 2004 , 2006 ; Brelidze and Magleby, 2005 ; Wilkens and Aldrich, 2006 ; Tang et al, 2009 ), are quite tolerant for large side-chain substitutions in the pore.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that permeant ions, such as thallium, can affect BK channel activation further led to the notion that the BK channel's activation gate may exist near or at the selectivity filter (21). A direct determination of the state dependence of ion accessibility at the selectivity filter using small cysteine modification reagents like cadmium and silver, as previously done in CNG channels (22), has been hampered by the complexity of BK channels, which have numerous endogenous cysteine residues whose modifications affect channel functions (23,24). Thus, it is important to explore alternative approaches to localizing the activation gate in BK channels.…”
mentioning
confidence: 99%
“…Ag + was found to affect the cell viability and morphology of skin fibroblasts and keratinocytes [Hidalgo et al, ]. Zhou et al showed that Ag + strongly inhibited the properties of Ca 2+ ‐activated K + channels, a widely expressed and physiological important channel [Zhou et al, ]. Furthermore, Ag + induced oxidative stress through the generation of reactive oxygen species and/or by impairing glutathione, an important cellular antioxidant [Cortese‐Krott et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Additional Supporting Information may be found in the online version of this article. Grant sponsor: JSPS KAKENHI; Grant numbers: 24510084 and 25340048. strongly inhibited the properties of Ca 21 -activated K 1 channels, a widely expressed and physiological important channel [Zhou et al, 2010]. Furthermore, Ag 1 induced oxidative stress through the generation of reactive oxygen species and/or by impairing glutathione, an important cellular antioxidant [Cortese-Krott et al, 2009].…”
Section: Introductionmentioning
confidence: 99%